Side‐swiped: ecological cascades emanating from earthworm invasions. Issue 9 (28th August 2019) - Frelich, Lee E; Blossey, Bernd; Cameron, Erin K; Dávalos, Andrea; Eisenhauer, Nico; Fahey, Timothy; Ferlian, Olga; Groffman, Peter M; Larson, Evan; Loss, Scott R; Maerz, John C; Nuzzo, Victoria; et al.
Abstract : Non‐native, invasive earthworms are altering soils throughout the world. Ecological cascades emanating from these invasions stem from rapid consumption of leaf litter by earthworms. This occurs at a midpoint in the trophic pyramid, unlike the more familiar bottom‐up or top‐down cascades. These cascades cause fundamental changes ("microcascade effects") in soil morphology, bulk density, and nutrient leaching, and a shift to warmer, drier soil surfaces with a loss of leaf litter. In North American temperate and boreal forests, microcascade effects can affect carbon sequestration, disturbance regimes, soil and water quality, forest productivity, plant communities, and wildlife habitat, and can facilitate other invasive species. These broader‐scale changes ("macrocascade effects") are of greater concern to society. Interactions among these fundamental changes and broader‐scale effects create "cascade complexes" that interact with climate change and other environmental processes. The diversity of cascade effects, combined with the vast area invaded by earthworms, leads to regionally important changes in ecological functioning.